Human resources practices in small medium enterprise within creative industry sector - Paramitha, Widya; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2016)
In years, small medium enterprise grew very fast in Indonesia and it is the pillar of indonesian economy. among those small medium enterprise, creative industry become the dark horse. They contributes about 7,05 percent of PDB, 10,72 percent of employment. Creative industry is also helps to grow regional economy, which resulted in increase Indonesian foreign exchange and export. Despite the enormous growth of small medium enterprise within creative industry, it is not supported by their human resources. Human resources in small medium enterprise is often being ignored thus it become the challenge to company to make sure they have the right people. The final project is about human resource practices in the small medium enterprise within creative industry. There are five representatives of companies as research objects. Qualitative research was used in the final project to discover human resources practices in small medium enterprise within creative industry, impact of human resource practices and suggestion to improve human practices in small medium enterprise. Interview and observation are used to get the objective of the final project. The result of this final project is generic model of human resources practices in small medium enterprise and a model concept to improve its human resources practices.Â  Â